2017
DOI: 10.1039/c7nr02999c
|View full text |Cite
|
Sign up to set email alerts
|

Probing the modulated formation of gold nanoparticles–beta-lactoglobulin corona complexes and their applications

Abstract: Understanding interactions between proteins and nanoparticles (NPs) along with the underlying structural and dynamic information is of utmost importance to exploit nanotechnology for biomedical applications. Upon adsorption onto the NP surface, proteins form a well-organized layer that dictates the identity of the NP-protein complex named corona and governs its biological pathways. Given the high biological relevance, in-depth molecular investigations and applications of NPs-protein corona complexes are still … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 84 publications
3
20
1
Order By: Relevance
“…Proteins like albumins are exhaustively documented to have high binding a nities to metals and form corona layers 30,34 , which are an ideal model probe to provide an appropriate distance for enhancement and prevent uorophores in close proximity to the plasmonic surface from quenching. Using uorophorelabeled BSA, we scrutinized the macroscopic enhancement on a broad spectral range of uorescence across the visible window (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Proteins like albumins are exhaustively documented to have high binding a nities to metals and form corona layers 30,34 , which are an ideal model probe to provide an appropriate distance for enhancement and prevent uorophores in close proximity to the plasmonic surface from quenching. Using uorophorelabeled BSA, we scrutinized the macroscopic enhancement on a broad spectral range of uorescence across the visible window (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It is then interrogated whether the uorescence enhancement of AgNIS was due to broad spectral surface plasmon resonance, rather than merely more surface-absorbed molecules, on the grounds that AgNIS could have a slightly larger effective surface area as well as notable protein-nanostructure interactions 30 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…They also found that the HSA-AuNP binding induces the flexibility and structural changes of HSA, which allosterically influences the binding affinity of HSA to fatty acids, thyroxin, and metals [ 24 ]. Yang et al simulated beta-lactoglobulin that was bound to AuNP and determined its binding site and structural change, which are interpreted by electrostatic interactions [ 25 ]. Tollefson et al simulated cytochrome c that was bound to a mercaptopropionic acid-functionalized AuNP and determined the preferred binding orientations of adsorbed proteins ( Figure 2 ) [ 26 ].…”
Section: Conformation Binding Site and Strength Of Plasma Proteins On The Nanoparticlementioning
confidence: 99%
“…The literature offers several examples of MD simulations of protein adsorption on different materials, such as graphene sheets (Chong et al, 2015), carbon nanotubes (Ge et al, 2011; Gu et al, 2015), gold nanoparticles/surfaces (Wang et al, 2013; Brancolini et al, 2014; Tavanti et al, 2015; Bellucci et al, 2016; Yang et al, 2017; Ma et al, 2018), hydroxyapatite surfaces (Dong et al, 2007, 2011), fullerenes (Leonis et al, 2015), titanium oxide surfaces (Utesch et al, 2011; Mudunkotuwa and Grassian, 2014), and molybdenum disulfide (Gu et al, 2018), highlighting the specific interactions behind the binding and the attainment of structural changes. Interestingly, there are no relevant computational studies of protein adsorption on polymer surfaces.…”
Section: Applications For Nanomaterial–biology Interactionsmentioning
confidence: 99%